Model Pembelajaran Snowball Throwing pada Mata Pelajaran TIK Kelas VII di SMP N 39 Semarang - Su'indayah, Siti; Sukamta, Sri; Suryono, Suryono (Edu Komputika Journal, 2016)
This research is motivated because the learning of ICT is still using the lecture method that is one direction and, teachers are one - the only source of information for students. So that students become passive and less active learning outcomes achieved less than the maximum. One effort to overcome this problem is by using Snowball Throwing learning model that aims to determine the activity and student learning outcomes.This study design using quasi-experimental design to study design pretest-posttest control group design. The samples in this study using cluster random sampling technique. And obtained VIID grade students as an experimental class and class VIIA as the control class. Techniques used in data collection that documentation, observation and tests.The results showed that the average activeness in class experiments of 80.07% with both categories. While the value - average learning outcomes of students in the experimental class increased to 83.03 to test the gain obtained at 0.558%. The conclusion that Snowball Throwing learning model can enhance the activity and student learning outcomes. It is advisable for most teachers use these models on the subjects that diampunya so that the desired learning outcomes achieved.